2010
DOI: 10.1111/j.1755-3768.2009.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular blood flow and oxygen delivery to the retina in primary open‐angle glaucoma patients: the addition of dorzolamide to timolol monotherapy

Abstract: ABSTRACT.Purpose: To assess the effects of adding dorzolamide to timolol monotherapy on ocular haemodynamics and retinal oxygen saturation in patients with primary open-angle glaucoma (POAG).Methods: Twenty-four patients (12 healthy, 12 with POAG) were treated with dorzolamide ⁄ timolol combination (DT) versus timolol maleate 0.5% twice daily in a randomized, crossover, double-blind study conducted over a period of 18 months. Patients received each treatment for 8 months then crossed over to the other treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…Studies using various retinal oximetry devices to measure the oxygen saturation of the retinal vasculature in glaucoma have been reported. [12][13][14][15][16][17][18][19][20] Hyperspectral imaging combines spectroscopy with digital imaging whereby spectral data (using numerous contiguous wavelengths of light) are obtained in every pixel of an image plane. An oximetry study of the retinal vascular network using a hyperspectral imaging system (images acquired using more than three contiguous wavelengths) in glaucoma has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using various retinal oximetry devices to measure the oxygen saturation of the retinal vasculature in glaucoma have been reported. [12][13][14][15][16][17][18][19][20] Hyperspectral imaging combines spectroscopy with digital imaging whereby spectral data (using numerous contiguous wavelengths of light) are obtained in every pixel of an image plane. An oximetry study of the retinal vascular network using a hyperspectral imaging system (images acquired using more than three contiguous wavelengths) in glaucoma has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Some data support increased blood flow and the enhancement of OBF regulation with carbonic anhydrase inhibitors. Several studies have shown dorzolamide's ability to increase various measures of OBF parameters, [10][11][12] although other studies failed to show similar effect. 13,14 Dorzolamide's vasodilatory effects might be explained by induced acidosis in local tissues.…”
mentioning
confidence: 99%
“…Our study findings may be explained by the vasodilatative effect of dorzolamide. Dorzolamide hydrochloride is perhaps the most vasoactive topical glaucoma treatment and several studies have shown it to increase various measures of ocular blood flow parameters [19,20,21,22,23,24], although other studies have failed to show similar effect [25,26,27]. Several authors when analysing normal subjects found that a single instillation of dorzolamide showed no significant effects on the blood flow through major retinal vessels [28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…showed that addition of dorzolamide to timolol monotherapy decreases IOP and increases retinal blood flow in the superficial retinal vasculature in both glaucomatous and healthy patients. The combination of increased retinal blood flow with consistent oxygen saturation may potentially increase oxygen delivery to the retina [38]. …”
Section: Discussionmentioning
confidence: 99%